Selecting Various Industrial Competitors Affect The Risk Level of Viet Nam Manufacturing Material Industry During and After The Global Crisis 2007-2009 - Ngoc Huy, Dinh Tran (Journal of Entrepreneurship, Business and Economics; Vol 4 No 1 (2016), 2016)
Using a one factor model, this paperwork estimates the impacts of the size of firms’ competitors in the manufacturing material industry on the market risk level, measured by equity and asset beta, of 99 listed companies in this category. This study identified that the risk dispersion level in this sample study could be minimized in case the competitor size doubles (measured by equity beta var of 0,293). Beside, the empirical research findings show us that asset beta max value increases from 1,162 to 1,445 when the size of competitor doubles. Last but not least, most of beta values are acceptable ex-cept a few exceptional cases. Ultimately, this paper illustrates calculated results that might give prop-er recommendations to relevant governments and institutions in re-evaluating their policies during and after the financial crisis 2007-2011. Research paper Reference to this paper should be made as follows: Huy. D. T. N. (2016). “Selecting Various Indus-trial Competitors Affect The Risk Level of Viet Nam Manufacturing Material Industry During and After The Global Crisis 2007-2009”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 1, pp. 108–127.